Effectiveness of a Camping Diabetes Program at Map Ta Phut Hospital, Rayong Province - Pasingchob, Winai (Journal of Health Science of Thailand, 2017)
This quasi experimental research was to assess the effectiveness of diabetes camping programs of type II diabetes patients at Map Ta Phut hospital, Rayong province between March and September 2011. The samples were type II diabetes patients that glycosylated hemoglobin level (HbA1c) exceeding 7 percent. They were divided into 2 groups. An experimental group of 30 patients was given a camping diabetes program and a control group of 30 patients received service at the diabetic clinic in hospital. The experimental group were selected based on an inclusion criteria and their consent. The instruments consisted of a camping diabetes program and a questionnaire of diabetic controlling behaviors. The statistic used for analyzing data were frequency, percentage, mean, standard deviation, independent t-test and paired t-test. The result of the study showed that the mean diabetic controlling behavioral score of the experimental group after the camping programs 3 months was significantly higher than before the camping programs at <0.01. The means HbA1c levels of the experimental group after the camping programs 3 months and 6 months were significantly lower than those before the camping programs and lower than those of the control group at <0.01.